Contribution to the Pipunculidae fauna of Spain (Diptera). - De Meyer, Marc (Contributions to Entomology = Beiträge zur Entomologie, 1997)
This study is mainly based on material of Pipunculidae collected in two localities in Spain: Pina de Ebro (Zaragoza) and Moraira (Alicante). Eleven new species are described: Eudorylas blascoi, E. dilatatus, E. falcifer, E. mediterraneus, E. monegrensis, E. tumidus, E. wahisi, Tomosvaryella hildeae, T. hispanica, T. resurgens, and T. sepulta. An updated checklist for the Spanish pipunculid fauna is given and the phenology and zoogeographical affinities are shortly discussed. Nomenclatural Acts blascoi de Meyer, 1997 (Eudorylas), spec. n. dilatatus de Meyer, 1997 (Eudorylas), spec. n. falcifer de Meyer, 1997 (Eudorylas), spec. n. mediterraneus de Meyer & Ackland, 1997 (Eudorylas), spec. n. monegrensis de Meyer, 1997 (Eudorylas), spec. n. tumidus de Meyer, 1997 (Eudorylas), spec. n. wahisi de Meyer, 1997 (Eudorylas), spec. n. hildeae de Meyer, 1997 (Tomosvaryella), spec. n. hispanica de Meyer, 1997 (Tomosvaryella), spec. n. resurgens de Meyer, 1997 (Tomosvaryella), spec. n. sepulta de Meyer, 1997 (Tomosvaryella), spec. n.